The Problem of Diarrhoeal Disease Children - Michael Gracey (Paediatrica Indonesiana, 1978)
In Western Austnalia, diarrheal disease in Aboriginal children found inhalf cases of malnutrition, sugar intolerance in 25% of patients and approximately 50% showed high rates of infection and infestation. The most commonly isolated are Giardia lamblia, Enteropathogenic E. Coli, Salmonellaea and Shigellae.The mortality rate of diarrhoeal disease is maro than 5%, which is severaltimes than white children. The cause of death are hypokalemia, hypoglycaemia, delayed rehydration treatment, the high incidence of malnutrition and sugar intolerance.To improve and solving the problem the prime aim should be preventionby upgrading many factors including maternal nutrition, promotion of breast feeding, standard of living, nutritional and hygiene education and related socioeconomic condition, the availability of skilled medical and nursing facilities.